2017
DOI: 10.3389/fped.2017.00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparative, Prospective, Case–Control Study of Open versus Laparoscopic Pyeloplasty in Children with Ureteropelvic Junction Obstruction: Long-term Results

Abstract: IntroductionWe compare open pyeloplasty (OP) versus laparoscopic pyeloplasty (LP) in children in a multicenter, prospective, case–control study.Materials and methodsFrom May 2007 to March 2009, a program was established at Hospital Garrahan, the reference center, to perform LP with a mentoring surgeon that would attend the institution once a month. Every new case of ureteropelvic junction obstruction (UPJO) diagnosed in the reference institution was offered to participate in the study. If the patient was enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Logistic regression analysis however revealed that the risk for complications was independent from the surgical technique applied and the age of the patients at surgery, which is in line with other reports. 15,26,31 Moreover, the frequency of re-do pyeloplasties (2.2%) as a main complication was comparable to that of others (3.1%) underlining the representativeness of our study cohort and the good quality of medical care for UPJO in Germany. 32 To date, there is no defined specialization for pediatric urology in Germany.…”
Section: Discussionsupporting
confidence: 73%
“…Logistic regression analysis however revealed that the risk for complications was independent from the surgical technique applied and the age of the patients at surgery, which is in line with other reports. 15,26,31 Moreover, the frequency of re-do pyeloplasties (2.2%) as a main complication was comparable to that of others (3.1%) underlining the representativeness of our study cohort and the good quality of medical care for UPJO in Germany. 32 To date, there is no defined specialization for pediatric urology in Germany.…”
Section: Discussionsupporting
confidence: 73%
“…Although most series report longer operative time in LP, (mean 155-240min) (3,8,11,16) we had spent a mean of 107min., which may be near the open procedures time. Previous adult experience, same team, routine and focusing on simplifying every step certainly play a role in the operative time.…”
Section: Discussionmentioning
confidence: 82%
“…In spite of that, the argument of open procedure through small incisions has been still supported by some, who do not consider that even small scars grow with patients development and may cause dissatisfaction later. Concerning pain related to open small incision, it may be underestimated in small children (2,6,8,16).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that LP has the superiority, while other studies showed no extra benefits. [ 7 8 ] There are limited data that substantially uphold one type over the other. This meta-analysis study aimed to assess the feasibility and effectiveness of redo LP (RLP) versus that of redo open pyeloplasty (ROP) in children with SUPJO, in terms of operative time, LOS, success rate, and postoperative complications (urine leakage) and to evaluate the quality of proof in the literature and provide accurate clinical information.…”
Section: Introductionmentioning
confidence: 99%